Understanding the Effects of Primary and Secondary Doping via Post-Treatment of P-Type and N-Type Hybrid Organic–Inorganic Thin Film Thermoelectric Materials - Rubio-Govea, Rodrigo; Felix, Roberto; Wilks, Regan G.; Bär, Marcus; Mazzio, Katherine A. (Advanced Electronic Materials, 2023)
Hybrid organic/inorganic materials have emerged as promising thermoelectric (TE) materials since they inherit the individual strengths of each component, enabling rational materials design with enhanced TE performance. The doping of hybrid TE materials via post-treatment processes is used to improve their performance, but there is still an incomplete understanding of the elicited effects. Here, the impact of different doping methods on the thin film TE performance of p-type Te/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and n-type Ag2Te/PEDOT:PSS hybrid materials is investigated. Primary doping through acid–base and charge transfer processes using H2SO4 and tetrakis(dimethylamino)ethylene, respectively, and the effects of secondary doping using ethylene glycol is examined. Through a combination of Hall effect measurements, hard X-ray photoelectron spectroscopy, and Raman spectroscopy, variations in the charge carrier concentration, mobility, and overall TE performance are related to the morphological and chemical structure of the hybrid materials. This study provides an improved understanding of the effects that different post-treatments have on hybrid materials and shows that the impact of these post-treatments on pure PEDOT:PSS does not always apply to hybrid systems. These new insights into post-treatment effects on hybrid materials is expected to facilitate further enhancement of their performance as electronic materials in general and thermoelectric materials in particular.
CRIS-Team Scopus Importer:2023-05-19
Keywords: hybrid materials; PEDOT:PSS; post-treatment; silver telluride; tellurium; thin film thermoelectric